Molecular identification and expression analysis of four Lysin motif (LysM) domain-containing proteins from turbot (Scophthalmus maximus). Issue 89 (June 2019) - Zhao, Chunyan; Jiang, Guangpeng; Zhou, Shun; Wang, Guodong; Sha, Zhenxia; Sun, Yongjun; Xiu, Yunji
Abstract: Lysin motif (LysM) is involved in chitin, peptidoglycan and other structurally-related oligosaccharides recognition and binding, and it is important for the biological processes of responsing to bacterial and viral infections and pathogen defense. LysM is also a widely spread protein, ranging from prokaryotes to eukaryotes, including bacteria, plants and mammals. However, research of LysM in teleosts especially in marine fish was rarely scarce. In the present study, four novel LysM domain-containing proteins in turbot ( Scophthalmus maximus ), named as SmLysMd1, SmLysMd2, SmLysMd3, and SmLysMd4, were cloned and identified firstly. The full-length cDNA of SmLysMd1 was 1235 bp with a 678 bp ORF, capable of encoding a peptide of 225 amino acids. The complete cDNA sequence of SmLysMd2 was 1273 bp, and contained a 675 bp ORF, encoding a predicted protein of 224 amino acids. The full-length of SmLysMd3 cDNA was 2132 bp, containing a ORF of 987 bp, with a ORF of encoding 328 amino acids. The full-length SmLysMd4 cDNA was 1115 bp contained a 888 bp ORF, encoding 295 amino acids. And all the four predicated proteins contained a specific LYSM domain. Moreover, SmLysMd1 and SmLysMd2 belong to the intracellular non-secretory types, and SmLysMd3 and SmLysMd4 belong to the anchored transmembrane types. In addition, the four SmLysMd were ubiquitously expressed in all the examined tissues. Moreover, the SmLysMds levels were up-regulated in muscle and liver, and had a reduce tendency immediately in different degree following Vibrio vulnificus challenge, indicating that the turbot LysM could be participant in the immune responses to bacterial infections. The present result of LysM in turbot for the first time in a marine fish will provide foundation knowledge for the functions studies of LysM in immune responses. Further studies should be carried out to better understand their immune mechanism in turbot and other teleosts. Highlights: Four transcripts of LysMd from turbot were cloned and characterized. Four SmLysMds were ubiquitously expressed in all tested tissues. Four SmLysMds were up-regulated after challenged with V. vulnificus. SmLysMds may play important roles during immune responses. This study provides foundation knowledge for their immune-related functions.